Aberrant Intraregional Brain Activity and Functional Connectivity in Patients With Diarrhea-Predominant Irritable Bowel Syndrome - Chen, Xiao-Fei; Guo, Yun; Lu, Xing-Qi; Qi, Le; Xu, Kuang-Hui; Chen, Yong; Li, Guo-Xiong; Ding, Jian-Ping; Li, Jie (Frontiers in Neuroscience, 2021)
Background and Purpose: The appearance and aggravation of diarrhea-predominant irritable bowel syndrome (IBS-D) have proven to be closely related to psychosocial factors. We aimed to measure altered spontaneous brain activity and functional connectivity (FC) in patients with IBS-D using resting-state functional magnetic resonance imaging (RS-fMRI) and to analyze the relationship between these parameters and emotional symptoms. Methods: Thirty-six adult IBS-D patients and thirty-six demographic-matched healthy controls (HCs) underwent RS-fMRI scans. After processing RS-fMRI data, the values of the amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) of the two groups were compared. The abnormal regions were selected as the regions of interest to compare whole-brain seed-based FC between the groups. The relationships between RS-fMRI data and mood and gastrointestinal symptoms were analyzed using correlation and mediation analyses. Results: Compared with HCs, IBS-D patients showed increased ALFF in the right cerebellum posterior lobe, the right lingual gyrus/calcarine, the right postcentral gyrus, the right superior frontal gyrus (SFG), and middle frontal gyrus (MFG), with decreased ALFF in the right inferior parietal lobule, the right striatum, the right anterior cingulated cortex, the right insula, the right hippocampus, the right thalamus, the right midbrain, and the left precuneus. IBS-D patients showed increased ReHo in the bilateral lingual gyrus/calcarine, the bilateral SFG, the right MFG, and the right postcentral gyrus, with decreased ReHo in the orbital part of the left inferior frontal gyrus and the right supplementary motor area. Patients showed enhanced FC between the left precuneus and the bilateral orbitofrontal cortex (OFC). There was a positive correlation between increased ALFF values in the right midbrain and anxiety-depression symptoms in IBS-D patients, and the mediating effect of gastrointestinal symptoms indirectly caused this correlation. Conclusions: IBS-D patients had dysregulated spontaneous activity and FC in regions related to pain regulation and emotional arousal involved in prefrontal–limbic–midbrain circuit and somatosensory processing. The development of mood disorders in IBS-D patients may be partly related to the dysfunction of components in the dopamine pathway (especially the midbrain, OFC) due to visceral pain.